New-Onset Postoperative Seizures in Patients With Diffuse Gliomas: A Risk Assessment Analysis - Li, Lianwang; Li, Guanzhang; Fang, Shengyu; Zhang, Kenan; Huang, Ruoyu; Wang, Yinyan; Zhang, Chuanbao; Li, Yiming; Zhang, Wei; Zhang, Zhong; Jin, Qiang; Zhou, Dabiao; et al. (Frontiers in Neurology, 2021)
Objective Glioma-related epilepsy (GRE) is the most common presenting sign of patients with diffuse glioma. According to clinical experience, new-onset postoperative seizures can be observed even in patients without preoperative GRE. The current study mainly aimed to explore the risk factors of new-onset postoperative seizures in those patients. In addition, the prognostic value of new-onset postoperative seizures was also discussed. Methods Data of 313 patients without GRE were retrospectively reviewed. Chi-square test or Fisher’s exact test were first performed to compare categorical variables between patients with new-onset postoperative seizures and those without. Subsequently, binary logistic regression analysis was conduct to further assess risk factors of new-onset postoperative seizures. Kaplan-Meier and Cox analysis was used to investigate the prognostic value of new-onset postoperative seizures for progression-free survival (PFS) and overall survival (OS). Results Patients with low-grade tumors (p=0.006), isocitrate dehydrogenase 1 (IDH1) mutation (p=0.040) or low Ki-67 expression (p=0.005) showed a higher incidence of new-onset postoperative seizures. IDH1 mutation was identified as the only independent predictor for new-onset postoperative seizures (OR, 2.075; 95% CI, 1.051–4.098; p=0.035). Additionally, new-onset postoperative seizure occurrence was demonstrated as an independent predicter of prolonged OS (OR, 0.574; 95% CI, 0.335-0.983; p=0.043), while younger age, gross total resection, low-grade and IDH1 mutation were independently correlated with prolonged OS and PFS. Conclusions IDH1 mutation is an independent predictor for new-onset postoperative seizures in patients without preoperative GRE. Moreover, new-onset postoperative seizures can independently predict prolonged OS in those patients. The results of the current study can contribute to improving the individualized management of diffuse glioma.